'New' Universities, Internationalisation and university rankings - Kennedy, Robert T., Prof.; Zuraidah Mohd Zain, Dr. (Universiti Malaysia Perlis, 2009)
Internationalisation of higher education, the main theme, is specifically directed at ‘new’ Universities and in particular Malaysia; however the issues and suggestions are applicable to any recently formed university and even to some of the older Institutions. A brief historical comparison shows that ‘new’ as applied to universities can have entirely different meanings. The wide ranging application of the terminology ‘Internationalisation’ requires a move towards a more application specific definition that is driven by universities rather than being the driver: a new definition is proposed. Internationalisation with respect to university age and size and related university rankings demonstrates the challenge for new universities. Consideration is given to the importance, needs and perceived risks of higher education internationalisation. The added dimension of ‘international orientation’, an international ranking systems factor, and the possible influence on the university approach to Internationalisation is discussed. Ranking pros and cons for ‘new’ universities to enter THES-like league-table ‘competitions’, and whether or not they can compete on a level playing ground with established universities are investigated. University in toto rankings are compared with subject and individual discipline ratings to support new university development in stages, and the need for a discipline based indicator system. A 3-stage (recognised, respected, ranked) 3- pathways (National, Regional, International) structured strategic planning approach to internationalisation is proposed. A brief introduction to the Malaysian Technical University System and UniMAP precedes a case study of internationalisation at UniMAP. Throughout the text Ministry of Higher Education, Malaysia recommendations [8] are quoted to ensure that internationalisation activities, suggestions and recommendations are in line with the development and direction of higher education in Malaysia.